High residue bio-based structural–functional integration epoxy and intrinsic flame retardant mechanism study. Issue 71 (16th December 2019) - Zhou, Ji; Heng, Zhengguang; Zhang, Haoruo; Chen, Yang; Zou, Huawei; Liang, Mei
Abstract : Research on structural–functional integrated polymers has become an inevitable trend in modern materials science. An intrinsic flame-retardant epoxy with superior performance and reusability is of great application value in the near future. Abstract : Research on structural–functional integration of polymers has become an inevitable trend and development orientation in modern materials science. An intrinsic flame-retardant epoxy with superior mechanical properties and reusability is of great application value as a composite matrix and structural material. We newly synthesized two bio-based epoxy resins, VSE and VDE, the Young's modulus of product cured by DDM (4, 4-diaminodiphenyl methane) achieve 5013 MPa and 4869 MPa, respectively. The LOI values of VSE and VDE were 38.7% and 34.5% respectively and both meet UL-94 V-0 rating. High char residue at 800 °C (34.5% and 28.0%, respectively) means a superior thermal stability which conventional epoxies are unreachable. Besides, cured VDE have convenient processability which can be re-shape as heating up and retain complete structural performance after cooling to room temperature. Furthermore, thermogravimetric analysis coupled with infrared spectroscopy (TGA-IR) and energy dispersive X-ray spectroscopy (EDS) were used to assist scanning electron microscopy (SEM) to investigate the intrinsic flame-retardant mechanism. In this work, the effect and process of nitrogen–phosphorus synergy on flame retardant is revealed finally. These results indicate the newly prepared epoxy has excellent flame retardancy, mechanical properties and recyclability which opens new possibilities in practical applications of epoxy such as coatings, potting or composite matrix in the near future.